Innovation to Improve Critical Thinking Skills in the Generation Z using Peeragogy as a Learning Approach and Artificial Intelligence (AI) as a Tool - Baskoro, Gembong; Mariza, Ita; Sutapa, I Nyoman (Institute of Research and Community Outreach - Petra Christian University, 2023)
The current generation, known as generation Z (Gen Z), is a generation that lives and is familiar with information technology in everyday life, including but not limited to learning purposes. Gen Z is characterized by teamwork in cyberspace and solving problems. Gen Z can also adopt artificial intelligence (AI) technology as their learning tool. Meanwhile, Gen Z faces the challenge of acquiring 21st-century skills requiring higher-order thinking (HOTS). This paper will focus on learning skills, especially critical thinking (CT). For this reason, it is essential to improve the competency of CT skills in Gen Z by using a model that combines the 7E learning cycle with peeragogy learning approach and adopting the latest AI applications as a tool. This model will contribute to the theoretical and practical use of AI apps for education, particularly the role of correct utilization of AI. Additionally, it can be misused to improve learning skills, especially CT skills. The results carried out in class show AI's effectiveness in improving CT skills for Gen Z, especially the role of AI in the back-end learning process, namely to verify and validate understanding. This paper suggests that AI apps should be controlled if used in the front-end learning process, especially at the exploration stage, to improve CT skills. Without controlling the AI apps, they can reduce learners' ability to explore a topic according to their creativity and criticality.